2014
DOI: 10.1071/an12356
|View full text |Cite
|
Sign up to set email alerts
|

Wild dog control impacts on calf wastage in extensive beef cattle enterprises

Abstract: Abstract. Wild dogs (Canis lupus dingo and hybrids) are routinely controlled to protect beef cattle from predation yet beef producers are sometimes ambivalent as to whether wild dogs are a significant problem or not. This paper reports the loss of calves between birth and weaning in pregnancy-tested herds located on two beef cattle properties in south-central and far north Queensland for up to 4 consecutive years. Comparisons of lactation failures (identified when dams that previously tested pregnant were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 26 publications
(31 reference statements)
1
60
0
Order By: Relevance
“…Possums (53% occurrence), macropods (29% occurrence) and rabbits (7% occurrence) were the three most frequently occurring prey species in dingo diets at Mt Owen, where dingoes switched seasonally between macropods and possums [47,48]. These observations suggest that baiting-induced changes to dingo populations can occur in some contexts, whereby large macropod prey can become unavailable (or uncatchable) to socially-fractured dingo populations exposed to baiting, which then must switch to alternative prey more easily captured [47,50]. In this case, dingoes exposed to baiting appeared to suppress populations of common possums, but not any other more threatened small mammal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possums (53% occurrence), macropods (29% occurrence) and rabbits (7% occurrence) were the three most frequently occurring prey species in dingo diets at Mt Owen, where dingoes switched seasonally between macropods and possums [47,48]. These observations suggest that baiting-induced changes to dingo populations can occur in some contexts, whereby large macropod prey can become unavailable (or uncatchable) to socially-fractured dingo populations exposed to baiting, which then must switch to alternative prey more easily captured [47,50]. In this case, dingoes exposed to baiting appeared to suppress populations of common possums, but not any other more threatened small mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…These findings broaden our understanding of the potential outcomes of predator control on prey fauna at lower trophic levels and have important implications for the management of dingoes and threatened fauna. Given the ineffectiveness of contemporary baiting practices at sustainably reducing dingo populations, it might be concluded that dingo control is a pointless waste of time, money and dingoes, which may even be counterproductive to cattle producers at times [50,92]. Importantly however, dingo control is typically undertaken to reduce or avert damage to livestock by dingoes, not to reduce dingo densities per se, and the relationship between dingo density and damage is not well understood Figure 11 Longer-term prey PTI trends in baited (solid lines) and unbaited (dotted lines) areas at Todmorden (see Table 4 for associated r and p values).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, perceived negative impacts of carnivores on livestock have historically been addressed by wholesale lethal control without any recognition of the positive impacts that carnivores may have on the herbivores that compete with livestock or the consequences of lethal control on livestock losses (e.g. Wicks and Allen, 2012;Allen, 2014;Allen, 2015a;Prowse et al, 2015;Allen, 2017). Treves et al (2016) and others (e.g.…”
Section: There Is a Dearth Of Applied-science Studiesmentioning
confidence: 99%
“…5). Although dingoes have been shown to kill over 30% or $200,000 worth of calves within a few months in NSA and other places in some circumstances (Fleming et al 2012b;Allen 2014), causing substantial economic losses to the beef industry (Gong et al 2009;Hewitt 2009), such losses do not occur routinely, but appear to be related to the reduced availability of preferred prey species in below-average rainfall years only (Eldridge et al 2002;Allen 2014Allen , 2015. Accounting for the indirect costs of dingo control associated with increased competition with kangaroos indicates that conservative dingo control practices may capitalize on the kangaroo-suppressive effects of dingoes, indirectly reducing competition for pasture and increasing the carrying capacity of cattle in arid and semi-arid systems (Fig.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The fundamental purpose of top-predator control in ecosystems dominated by grazing livestock is to increase livestock production. However, the direct and indirect effects of predator control on livestock production have not been well-studied in many places (for examples, see Allen and Sparkes 2001;Berger 2006;Hebblewhite 2011;Allen 2014). Predators often kill both livestock and competitors of livestock alike, suggesting that there may be merit in investigating the indirect benefits that predators may provide to livestock producers.…”
Section: Introductionmentioning
confidence: 99%